"Book Review: The Worth of Water by Matt Damon and Gary White". (13th December 2022) - Vinciguerra, Tebaldo
Abstract: Gary White and Matt Damon's recent book, The Worth of Water, details the challenges faced and insights gleaned while building a major microcredit initiative to improve access to safe water and/or sanitation. It was presented during the World Water Forum in Dakar (March 2022). I will describe the birth and evolution of this initiative, contextualizing it in the current concern for access to clean water, and attempting to highlight its main technical details (financing, organization, and reach). I will also try to offer some critical consideration (regarding access to drinking water as a human right) and perspective (on the possible development of the approach promoted by the book).